The yin/yang balance of the MHC-self-immunopeptidome - Santambrogio, Laura; Franco, Alessandra (Frontiers in Immunology, 2022)
The MHC-self immunopeptidome presented by professional antigen presenting cells is a cognate ligand for the TCRs expressed on both conventional and thymic-derived natural regulatory T cells. In regulatory T cells the TCR signaling associated with MHC-peptide recognition induce antigen specific as well as bystander immunosuppression. On the other hand, TCR activation of conventional T cells is associated with protective immunity. As such the peripheral T cell repertoire is populated by a number of T cells with different phenotypes and different TCRs which can recognize the same MHC-self-peptide complex resulting in opposite immunological outcomes. Herein, we will summarize what is known about regulatory and conventional T cell recognition of the MHC-self-immunopeptidome at steady state and in inflammatory conditions associated with increased T and B cell self-reactivity and how changes in the MHC-ligandome including epitope copy number and post-translational modifications can tilt the balance toward the expansion of pro-inflammatory or regulatory T cells.